2021
DOI: 10.3390/nu13062066
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Safety of a Novel Ketogenic Ester, Bis-Hexanoyl (R)-1,3-Butanediol: A Randomized Controlled Trial in Healthy Adults

Abstract: Nutritional ketosis is a state of mildly elevated blood ketone concentrations resulting from dietary changes (e.g., fasting or reduced carbohydrate intake) or exogenous ketone consumption. In this study, we determined the tolerability and safety of a novel exogenous ketone diester, bis-hexanoyl-(R)-1,3-butanediol (BH-BD), in a 28-day, randomized, double-blind, placebo-controlled, parallel trial (NCT04707989). Healthy adults (n = 59, mean (SD), age: 42.8 (13.4) y, body mass index: 27.8 (3.9) kg/m2) were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 60 publications
2
27
1
Order By: Relevance
“…Second, in Study 3 it was demonstrated that weight loss achieved over 6-weeks was a robust stimulus to uniformly decrease plasma BDNF regardless of the macronutrient distribution of the diet or level of ketosis. Thus, circulating BDNF levels can be modulated in healthy adults, but unlike the results from many animal studies [ 11 , 27 ] the results from our work do not support a major effect of nutritional ketosis achieved through a low-carbohydrate eating pattern or exogenous ketone consumption on plasma BDNF in healthy adults.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, in Study 3 it was demonstrated that weight loss achieved over 6-weeks was a robust stimulus to uniformly decrease plasma BDNF regardless of the macronutrient distribution of the diet or level of ketosis. Thus, circulating BDNF levels can be modulated in healthy adults, but unlike the results from many animal studies [ 11 , 27 ] the results from our work do not support a major effect of nutritional ketosis achieved through a low-carbohydrate eating pattern or exogenous ketone consumption on plasma BDNF in healthy adults.…”
Section: Discussioncontrasting
confidence: 99%
“…Ingestion in the fed state produces a rapid and dose-responsive increase in plasma [R-βHB] [ 39 , 106 ] e.g…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies demonstrate that a ketone monoester drink effectively improves glucose clearance in healthy young adults [59], and in participants with obesity [60]. Regarding longer term studies, two 1-month studies in which healthy participants consumed ketone esters daily found that despite regular elevations in βOHB, the ketone esters had no effect on body weight or body composition, fasting blood glucose, cholesterol, or triglyceride concentrations [52]. In a similar study design, patients with type 2 diabetes experienced modest improvements in markers of glycemic control, including mean blood glucose and HbA1c [61].…”
Section: Ketone Supplementsmentioning
confidence: 99%
“…For example, ingestion of a ketone monoester acutely reduces ghrelin (a gut hormone that stimulates the desire to eat), self-reported hunger, and enhances satiation [65]. Despite these promising findings acutely, longer term studies of ketone supplementation have reported no change in bodyweight [52], and therefore, the limited data available suggest that long-term ketone supplementation may not have an appreciable effect on caloric intake.…”
Section: Exogenous Ketones and Cardiometabolic Health In Humansmentioning
confidence: 99%